Fecal sludge treatment for resource recovery and biological hazard control: Phase partitioning, process intensification, and data-driven optimization - Xiaoyu Cai; Jialiang Gu; Yitian Li; Jun Nan; Defeng Xing (Chemical Engineering Journal, 2026)

Robust and enhanced precise baseline determination using spaceborne GNSS, accelerometer and intersatellite ranging measurements - Kai Shao; Tao Jiang; Chunbo Wei; Bin Yi; Defeng Gu (GPS Solutions, 2026)

Numerical Simulation of Large Deformation Movement Process of Underwater Slope Subjected to Seismic Loads: A Case Study from the St. Niklausen Landslide - Mingzhe Wei; Zhongde Gu; Ze Rong; Yang Liu; Yang Lu; Defeng Zheng; Tingkai Nian (Journal of Marine Science and Engineering, 2026)
Large deformation runout is a key factor in assessing the hazards posed by underwater landslides. However, conventional kinematic analyses often neglect both the progressive degradation of slope materials and the hydrodynamic response accompanying the interaction between the moving mass and the overlying water. Taking the well-documented St. Niklausen underwater landslide as a representative case, this study employs a coupled Eulerian–Lagrangian (CEL) model to investigate the earthquake-triggered initiation, large deformation movement, and hydrodynamic response of the landslide. A Python 2.7.15-based stress mapping method is developed to establish an accurate initial geostatic stress field for the irregular slope profile. The numerical model reproduces the principal stages of landslide initiation, runout, and deposition. The results reveal a progressive retrogressive failure mechanism in which successive sliding masses interact through a high-strength compression zone. The rear sliding mass continuously transfers compressive work to the frontal mass, thereby maintaining its downslope movement and indirectly promoting basal erosion to a maximum depth of approximately 6.2 m. In addition, rapid landslide motion generates pronounced vortical flow in the overlying water. These flow structures reflect the hydrodynamic response induced by landslide motion, although their net influence on basal resistance and final runout cannot be isolated from the present coupled simulation. These findings clarify the internal mechanical evolution of underwater landslide movement and characterize the accompanying hydrodynamic response, providing a methodological basis for assessing landslide mobility and related underwater hazards.

Real-time orbit determination of Sentinel-6A using different broadcast ephemeris error compensation methods - Aoming Wang; Chunbo Wei; Zhiyong Huang; Tao Jiang; Defeng Gu (Advances in Space Research, 2026)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

Precise baseline determination for the four-satellite InSAR constellation HT-01 with ambiguity resolution constraints - Dachen Peng; Shibo Guo; Defeng Gu; Kai Shao; Houzhe Zhang; Ruiyun Yang; Jufeng Lu; Jiangkai Liu; Haoseng Wang; LiuPeng Huang (Advances in Space Research, 2025)

A review of submarine landslides associated with rapid sedimentation - Zehao Wang; Defeng Zheng; Xingsen Guo; Zhongde Gu; Chenglin Yan; Tingkai Nian (Marine Georesources & Geotechnology, 2025)

Numerical investigation of the instability process in underwater sedimentary slopes subjected to seismic action - Tingkai Nian; Zehao Wang; Defeng Zheng; Zhongde Gu; Chenglin Yan; Xingsen Guo (Engineering Geology, 2025)

A method for improving the BDS3-based kinematic precise orbit determination of LEO satellites with single-receiver ambiguity resolution - Houzhe Zhang; Defeng Gu; Kai Shao; Bing Ju; Bin Yi; Zhiyong Huang; Haijun Tao (Advances in Space Research, 2025)

Precise baseline determination for InSAR formation-flying satellites based on spaceborne BDS-3 and GPS observations - Dachen Peng; Kai Shao; Defeng Gu; Houzhe Zhang; Zhiyong Huang; Bin Yi; Jubo Zhu (Advances in Space Research, 2025)

Editorial: Advances in autonomous ships (AS) for ocean observation - Xinyu Zhang; Yanlong Chen; Gorka Bidegain; Defeng Wu; Yanzhen Gu; Chengbo Wang (Frontiers in Marine Science, 2024)

Orbit determination of Earth-Moon libration point navigation constellation based on Inter-satellite links - Zheyu Xu; Kai Shao; Defeng Gu; Lisheng Tong; Lan Du; Chunbo Wei; Zicong An; Jubo Zhu (Advances in Space Research, 2024)

A Methodology to Evaluate the Real-Time Stability of Submarine Slopes under Rapid Sedimentation - Zehao Wang; Defeng Zheng; Zhongde Gu; Xingsen Guo; Tingkai Nian (Journal of Marine Science and Engineering, 2024)
Rapid sedimentation is widely recognized as a crucial factor in initiating the instability of submarine slopes. Once the slope fails, the subsequent landslide poses a significant threat to the safety of underwater infrastructures and potentially leads to severe damage to seabed pipelines, offshore foundations, and oil and gas exploitation wells. However, there is currently a lack of numerical methods to effectively assess the real-time stability of submarine slopes under rapid sedimentation. This study firstly employs a calibrated finite element (FE) model-change approach to reproduce the rapid sedimentation processes and proposes a concise method to calculate the safety factors for the real-time stability of sedimenting submarine slopes. Further, a parametric analysis is carried out to evaluate the effect of varying sedimentation rates on slope stability, and the critical sedimentation rate is numerically solved. Moreover, the effect of seismic events with different occurring times on the stability of rapidly sedimenting slopes is investigated in depth, and the most critical seismic loading pattern among various acceleration combinations is achieved. The results indicate that the presence of weak layers during sedimentation is a critical factor contributing to slope instability. The introduced rate of decrease in the safety factor proves valuable in assessing slope safety over a specific period. As the occurrence time of seismic events is delayed, the seismic resistance of the slope decreases, increasing the likelihood of shallower sliding surfaces. The findings offer insights into the mechanisms by which rapid sedimentation influences the stability of submarine slopes and provide valuable insights for predicting the potential instability of rapidly sedimenting slopes under specific seismic activity levels.

Sequential recovery of protein and ammonium from waste sludge and functional metabolism in a combined process of nutrient recovery electro-fermentation (NREF) - Jiayu Gu; Huihui Zhou; Jing Wang; Kun Feng; Guojun Xie; Bingfeng Liu; Defeng Xing (Resources, Conservation and Recycling, 2024)

An algorithm of dynamic temporal constraints for the mission series in deep space detectors - Yuheng Qi; Yuan Liu; Defeng Gu; Jubo Zhu (Advances in Space Research, 2024)

Enhanced orbit and baseline determination for formation-flying LEO satellites with spaceborne accelerometer measurements - Chunbo Wei; Kai Shao; Defeng Gu; Zheng Zhang; Jubo Zhu; Zicong An; Jian Wang (Journal of Geodesy, 2023)

Analysis of Tiangong-2 orbit determination and prediction using onboard dual-frequency GNSS data - Kai Shao; Defeng Gu; Bing Ju; Wenbin Wang; Chunbo Wei; Xiaojun Duan; Zhengming Wang (GPS Solutions, 2020)

A Path-Planning Strategy for Unmanned Surface Vehicles Based on an Adaptive Hybrid Dynamic Stepsize and Target Attractive Force-RRT Algorithm - Zhen Zhang; Defeng Wu; Jiadong Gu; Fusheng Li (Journal of Marine Science and Engineering, 2019)
It is well known that path planning has always been an important study area for intelligent ships, especially for unmanned surface vehicles (USVs). Therefore, it is necessary to study the path-planning algorithm for USVs. As one of the basic algorithms for USV path planning, the rapidly-exploring random tree (RRT) is popular due to its simple structure, high speed and ease of modification. However, it also has some obvious drawbacks and problems. Designed to perfect defects of the basic RRT and improve the performance of USVs, an enhanced algorithm of path planning is proposed in this study, called the adaptive hybrid dynamic stepsize and target attractive force-RRT(AHDSTAF-RRT). The ability to pass through a narrow area and the forward speed in open areas of USVs are improved by adopting the AHDSTAF-RRT in comparison to the basic RRT algorithm. The improved algorithm is also applied to an actual gulf map for simulation experiments, and the experimental data is collected and organized. Simulation experiments show that the proposed AHDSTAF-RRT in this paper outperforms several existing RRT algorithms, both in terms of path length and calculating speed.

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)

Enhanced cycle slip detection method for dual-frequency BeiDou GEO carrier phase observations - Bing Ju; Defeng Gu; Xiao Chang; Thomas A. Herring; Xiaojun Duan; Zhengming Wang (GPS Solutions, 2017)

Precise orbit and baseline determination for maneuvering low earth orbiters - Bing Ju; Defeng Gu; Thomas A. Herring; Gerardo Allende-Alba; Oliver Montenbruck; Zhengming Wang (GPS Solutions, 2017)

Dietary salt modulates the sodium chloride cotransporter expression likely through an aldosterone-mediated WNK4-ERK1/2 signaling pathway - Lingyun Lai; Xiuyan Feng; Defeng Liu; Jing Chen; Yiqian Zhang; Bowen Niu; Yong Gu; Hui Cai (Pflügers Archiv - European Journal of Physiology, 2012)